2001
DOI: 10.1037/1064-1297.9.4.372
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to novel environmental stimuli decreases amphetamine self-administration in rats.

Abstract: Researchers examined whether exposure to novel environmental stimuli reduces drug self-administration. Rats were trained to self-administer amphetamine on a fixed ratio (FR) 5 schedule of reinforcement and then were exposed to novel stimuli during the session. Responding was significantly decreased with exposure to novelty but returned to baseline levels on intervening nonexposure sessions. In 2 subsequent experiments, rats were exposed to novel plastic objects prior to the session. Immediately following expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
6
19
0
Order By: Relevance
“…In humans, prosocial behaviors such as physical activity and engaging in high sensation experiences may be effective in reducing drug use. These findings parallel those observed in rats (Klebaur et al, 2001b;Smith and Pitts, 2011), and results from monkeys suggest that enriching stimuli may decrease drug reinforcement (Nader et al, 2008). Not only do alternative appetitive stimuli reduce drug self-administration generally, the effectiveness of alternative stimuli may be greatest among individuals prone to addiction.…”
Section: Implications For Prevention and Treatment Of Drug Abusesupporting
confidence: 72%
“…In humans, prosocial behaviors such as physical activity and engaging in high sensation experiences may be effective in reducing drug use. These findings parallel those observed in rats (Klebaur et al, 2001b;Smith and Pitts, 2011), and results from monkeys suggest that enriching stimuli may decrease drug reinforcement (Nader et al, 2008). Not only do alternative appetitive stimuli reduce drug self-administration generally, the effectiveness of alternative stimuli may be greatest among individuals prone to addiction.…”
Section: Implications For Prevention and Treatment Of Drug Abusesupporting
confidence: 72%
“…The decrease in stimulant self-administration is generally believed to be due to response competition, with the nondrug reinforcer competing with the drug reinforcer (Higgins 1997). Recent research in our laboratory has demonstrated that novel stimuli present during the amphetamine self-administration session decrease the number of infusions earned (Klebaur et al 2001b), consistent with the hypothesis that novel environmental stimuli may be rewarding (Bardo et al 1996). Indeed, rats prefer novel stimuli over familiar stimuli in a variety of situations (Bevins and Bardo 1999;Hughes 1992;Nicholls et al 1992;Pierce et al 1990).…”
Section: Introductionmentioning
confidence: 59%
“…For example, in rats, exposure to novel environmental stimuli attenuated i.v. amphetamine self-administration Klebaur et al 2001), and access to running wheels reduced i.v. cocaine self-administration .…”
Section: Introductionmentioning
confidence: 99%